Analysis of Agroforestry Types and Their Contribution to Sustainable Agriculture in the Community Forest (HKm) Kibuk, Pagaralam City, South Sumatra: Analisis Tipologi Agroforestri dan Kontribusinya terhadap Pertanian Berkelanjutan di Hutan Kemasyarakatan (HKm) Kibuk, Kota Pagaralam, Sumatera Selatan - Deddy Permana; Supli Effendi Rahim; Asvic Helida; Jun Harbi (Journal of Global Sustainable Agriculture, 2025)
Agroforestry is a land management approach that combines agricultural crops with woody plants to improve land production and community well-being. This study seeks to examine the typology of agroforestry and its contribution in promoting sustainable agriculture within the Community Forest (HKm) Kibuk, located in Pagar Alam City, South Sumatra. The research methodology employed is a mixed methods approach, incorporating both qualitative and quantitative techniques. Data were collected using field observations, interviews with 23 members of the forest farmer group, and an analysis of land cover alterations from 2016 to 2020. The research findings indicate the implementation of six agroforestry types in HKm Kibuk, predominantly featuring coffee trees (Arabica and Robusta) with protective species like as avocado and acacia, in addition to understorey crops like horticultural vegetables. Complex agroforestry systems incorporating diverse shade tree species possess greater potential for enhancing ecosystem resilience and augmenting carbon sequestration capabilities than simplistic agroforestry models. The primary problems encountered are the farmers' lack technical expertise and restricted market access. Consequently, it is essential to adopt measures that augment farmers' capabilities via training, legislative incentives, and the fortification of financing schemes to ensure the sustainability of implemented agroforestry systems.